The Legal Status of Non-Muslims in the Shiite Fiqh and Iranian Laws (1906–2020) by Saeid Edalatnejad - Zahra Naghshband (Entangled Religions - Interdisciplinary Journal for the Study of Religious Contact and Transfer)
This contribution offers a review of The Legal Status of Non-Muslims in the Shiite Fiqh and Iranian Laws (1906–2020) by Saeid Edalatnejad (2023)